Biodiversity and community structure of mangrove gastropods across Karimunjawa National Park, Indonesia - MUHAMMAD ARIF ASADI; ANNAS TASYA WIDODO; ALIFYA NADHIRA JASMINE; DIAN ALIVIYANTI; MULIAWATI HANDAYANI (Society for Indonesian Biodiversity, 2026)
Abstract. Asadi MA, Widodo AT, Jasmine AN, Aliviyanti D, Handayani M. 2026. Biodiversity and community structure of mangrove gastropods across Karimunjawa National Park, Indonesia. Biodiversitas 27 (7): d270713. https://doi.org/10.13057/biodiv/d270713. Mangrove ecosystems sustain varied benthic communities that are crucial for nutrient cycling and ecosystem functionality. This research investigates the spatial distribution, abundance, and community structure of gastropods within the mangrove ecosystem of Karimunjawa National Park, Indonesia. At each of ten stations, three 10×10 m mangrove plots were established for mangrove density assessment, and within each plot, three 1×1 m subplots were used to sample gastropods during low tide in January 2025 (rainy season). A total of 1,146 individuals representing 7 families and 16 species were recorded. The highest densities were for the sulcate swamp whelk (Terebralia sulcata, 8.55 inds/m²) and the girdled horn snail (Cerithidea cingulata, 7.88 inds/m²) from the family Potamididae. The differences in Shannon-Wiener Diversity (H′: 0.82-1.70) and Pielou’s Evenness (J′: 0.68-0.91) among stations indicate spatial heterogeneity among stations, potentially linked to differing habitat conditions. Linear regression analysis showed a strong positive relationship between gastropod abundance and sediment organic matter (R²: 0.49, p<0.0001), while mangrove tree density had no significant effect (p: 0.52). Sediment organic matter was significantly associated with gastropod abundance, indicating that sites with higher organic matter tended to support greater gastropod abundance. This relationship suggests that sediment quality is an important driver of gastropod abundance, although additional environmental factors likely contribute to the remaining variation among sites. Therefore, this study provides baseline information for future monitoring of gastropod communities and contributes to understanding spatial patterns of mangrove gastropod communities in Karimunjawa National Park.